Toxoplasma gondii infection specifically increases the levels of key host microRNAs. - Gusti M Zeiner (PLoS ONE, 2010)
The apicomplexan parasite Toxoplasma gondii can infect and replicate in virtually any nucleated cell in many species of warm-blooded animals; thus, it has evolved the ability to exploit well-conserved biological processes common to its diverse hosts. Here we have investigated whether Toxoplasma modulates the levels of host microRNAs (miRNAs) during infection.Using microarray profiling and a combination of conventional molecular approaches we report that Toxoplasma specifically modulates the expression of important host microRNAs during infection. We show that both the primary transcripts for miR-17 approximately 92 and miR-106b approximately 25 and the pivotal miRNAs that are derived from miR-17 approximately 92 display increased abundance in Toxoplasma-infected primary human cells; a Toxoplasma-dependent up-regulation of the miR-17 approximately 92 promoter is at least partly responsible for this increase. The abundance of mature miR-17 family members, which are derived from these two miRNA clusters, remains unchanged in host cells infected with the closely related apicomplexan Neospora caninum; thus, the Toxoplasma-induced increase in their abundance is a highly directed process rather than a general host response to infection.Altered levels of miR-17 approximately 92 and miR-106b approximately 25 are known to play crucial roles in mammalian cell regulation and have been implicated in numerous hyperproliferative diseases although the mechanisms driving their altered expression are unknown. Hence, in addition to the implications of these findings on the host-pathogen interaction, Toxoplasma may represent a powerful probe for understanding the normal mechanisms that regulate the levels of key host miRNAs.